More than meets the eye: reconstructing women in women’s cinema. - Nurul Musfirah Abdul Talib. (2011)
The topic of this thesis has emerged out of my general observation of films, which are mostly made to suit the male spectatorial pleasure, and my disappointment at the often tiny representation of women’s significance in films that are independent of its relation to male’s desire. What inspires the idea of the thesis is the estranging sense of not quite belonging and being out of joint as a female spectator who witnesses women characters on screen that are often shaped and created to suit the seemingly inviolable desire of male spectatorship. I have chosen to discuss Gurinder Chadha’s Bend It Like Beckham and Mira Nair’s Monsoon Wedding to show that on the subject of women’s identity and sexuality, these female directors are able to disregard the conventional patriarchal cinematic codes that states women to be “obsessively subordinated to the neurotic needs of the male ego” (Herndi, 447), while incorporating the themes of diaspora and modernity to highlight how women’s identities are shaped upon their intercultural experiences within a modern, unbounded environment of possibilities. In this paper, I have attempted to discuss the ways in which Gurinder Chadha and Mira Nair have made use of editing and camera techniques to put forth the concepts of “subjectivity, desire and visual pleasure” that have introduced and legalized the female spectatorial desire, undoing the hetero-normative stereotypes so that women are no longer merely “the image”, for they are now regarded as the essential and not the “Other”.